Cars, Conduits, and Kampongs - Cot (Verhandelingen van het Koninklijk Instituut voor Taal-, Land- en Volkenkunde, 2015)
Cars, Conduits and Kampongs offers a wide panorama of the modernization of Indonesian cities between 1920 and 1960. In examining the multiple responses to innovations introduced by Western colonialism, the contributors demonstrate how modernization, urbanization, and decolonization were intrinsically linked. A full text Open Access version is also available.